Conceptual analysis of mental health according to Muslim Scholars for Stress Prevention Project (STOP) in Gombak - Ahmad, Nadzrah; Wan Yusoff, Wan Mazwati; Janon, Nazariah Shar'ie (2019)
The beginning of 2019, marked yet a new navigation of IIUM as a ‘Community-Engaged University’ by announcing its endeavours towards a set of society-based designed programmes which opens its wings for the public involvement and placing stakeholders as the main beneficiary at its wake. Engaging with the immediate vision of the University, the Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS) launched its Youth Empowerment Flagship to spearhead programs and interventions for youth in Gombak. Stress Prevention Project (STOP) was established under this flagship aiming at addressing and inculcating awareness on issues of stress among secondary school students of Gombak. Aligned with United Nation’s Sustainable Development Goals (SDG) – (No.3 and No.11) –, this project is navigated at improving the current state of mental hygiene in adolescents of the local area. The project aimed to produce a stress prevention module for secondary school students (adolescents) in Gombak.